Characterizing the Retinal Function of Psammomys obesus: A Diurnal Rodent Model to Study Human Retinal Function. (2nd January 2017) - Dellaa, Ahmed; Polosa, Anna; Mbarek, Sihem; Hammoum, Imane; Messaoud, Riadh; Amara, Soumaya; Azaiz, Rached; Charfeddine, Ridha; Dogui, Mohamed; Khairallah, Moncef; Lachapelle, Pierre; Ben Chaouacha-Chekir, Rafika
ABSTRACT: Purpose : To compare the retinal function of a diurnal murid rodent, Psammomys obesus, with that of Wistar albino rat and human subjects. Materials and methods : Adult Psammomys obesus were captured and transferred to the animal facilities where they were maintained at 25°C with standard light/dark cycles and natural halophilic plants, rich in water and mineral salts. Standard full-field photopic and scotopic electroretinograms were obtained. Results : The right eye of all animals displayed well detectable and reproducible scotopic and photopic electroretinogram (ERG) responses. Results were compared with those obtained from human subjects and Wistar rats. ERG measurement showed that the amplitudes of scotopic responses in Psammomys obesus are quite similar to those of human subjects. The amplitude of the photopic a-wave was comparable to that of humans and six times higher than that of the albino rat. The amplitudes of photopic b-wave, photopic oscillatory potentials (OPs), and 30 Hz flicker were all markedly larger in Psammomys obesus compared to those obtained from human subjects and Wistar rats. Furthermore, like the human photopic ERG, the photopic ERG of Psammomys obesus also includes prominent post b-wave components (i.e. i- and d-waves) while the ERG of Wistar rats does not. Conclusions : Our results suggest that the retinal function of Psammomys obesus, especially the cone-mediated function, shares several features with that of human subjects. We believe that Psammomys obesus represents an interesting alternative to study the structure and function of the normal and diseased retina in a human-like rodent model of retinal function.